Fabrication of Polycaprolactone/Polyurethane Loading Conjugated Linoleic Acid and Its Antiplatelet Adhesion - Minh, Ho Hieu; Hiep, Nguyen Thi; Hai, Nguyen Dai; Toi, Vo Van (International Journal of Biomaterials, 2017)
Polycaprolactone/polyurethane (PCL/PU) fibrous scaffold was loaded with conjugated linoleic acid (CLA) by electrospinning method to improve the hemocompatibility of the polymeric surface. Fourier Transform Infrared Spectroscopy (FT-IR) analysis and Scanning Electron Microscopy (SEM) observation were employed to characterize the chemical structure and the changing morphology of electrospun PCL/PU and PCL/PU loaded with CLA (PCL/PU-CLA) scaffolds. Platelet adhesion and whole blood clot formation tests were used to evaluate the effect of CLA on antithrombotic property of PCL/PU-CLA scaffold. Endothelial cells (EC) were also seeded on the scaffold to examine the difference in the morphology of EC layer and platelet attachment with and without the presence of CLA. SEM results showed that CLA supported the spreading and proliferation of EC and PCL/PU-CLA surface induced lower platelet adhesion as well as attachment of other blood cells compared to the PCL/PU one. These results suggest that electrospinning method can successfully combine the antiplatelet effects of CLA to improve hemocompatibility of PCL/PU scaffolds for applications in artificial blood vessels.